Essays on growth, structural transformation and education - Pereira, Luciene Torres de Mello (2016)
This thesis contains three chapters. The first chapter studies the emergence of slums as a common feature in a country's path towards urbanization, structural transformation and development. Based on salient micro and macro evidence of Brazilian labor, housing and education markets, we construct a simple model to examine the conditions for slums to emerge. We then use the model to examine whether slums are barriers or stepping stones for lower skilled households and for the development of the country as a whole. We calibrate our model to explore the dynamic interaction between skill formation, income inequality and structural transformation with the rise (and potential fall) of slums in Brazil. We then conduct policy counterfactuals. For instance, we find that cracking down on slums could slow down the acquisition of human capital, the growth of cities (outside slums) and non-agricultural employment. The impact of reducing housing barriers to entry into cities is also explored. The second chapter studies the impact of education and fertility in structural transformation and growth. In the model there are three sectors, agriculture, manufacturing and services. Parents choose optimally the number of children and their skill. Educational policy has two dimensions, it may or may not allow child labor and it subsidizes education expenditures. The model is calibrated to South Korea and Brazil, and is able to reproduce some key stylized facts observed between 1960 and 2005 in these economies, such as the low (high) productivity of services in Brazil (South Korea) which is shown to be a function of human capital and very important in explaining its stagnation (growth) after 1980. We also analyze how different government policies towards education and child labor implemented in these countries affected individuals' decisions toward education and the growth trajectory of each economy. The third chapter investigates how the positive assortative mating in the marriage market contributes to income inequality across households in Brazil. To adress this question, we analyze samples of hundreds of thousands of households from the Brazilian Census Bureau for the period 1970 to 2010. The positive assortative mating in a first moment does not affect negatively income inequality. However, from some counterfactual exercises, we show that the improvement in income distribution during this period could have been even better if the trend in the marriage market had not ocurred.